Preparation of Organosilicone Anti-Wear Coating on PDMS Membrane - ZHANG Min, LI Song-jing, LI Xiao-ping, NIE Gao-xing (Cailiao Baohu, 2021)
In order to improve the hardness and anti-wear property of Polydimethylsiloxane (PDMS) membrane, as well as to further expand the applications of microfluidic materials, the preparation method of organosilicone anti-wear coating on PDMS membrane was developed with Methyltrimethoxysilane (MTMS) and Phenyltrimethoxysilane (PTMS) as the main materials. Meanwhile, other materials such as methylacrylate sol with toughening effect and HCl catalyst were also added. The effects of different components on anti-wear property, hardness, adhesion, optical transmittance and high temperature resistance of the coating were tested, the ratio of each component in the coating was optimized. Results showed that the fabricated organosilicone anti-wear coating effectively improved the anti-wear property, hardness and high temperature resistance of PDMS membrane, which showed good adhesion with PDMS substrate and high transparency in visible light region. Therefore, the surface properties of the PDMS membrane were significantly enhanced.